Symbolic Convergence in A Social Movement: A Case of â€œPengumpulan Satu Juta Ktpâ€ by Teman Ahok - Angeline, Mia (Humaniora, 2016)
Internet plays an important role in modern social movements. One of the modern social movements succeeded in Jakarta was initiated by Teman Ahok named "Pengumpulan Satu Juta KTP Untuk Ahok". The article was a part of a larger research about cyberurban space in a social movement. Therefore, the research question was, ?how was imaginaries in cyberurban space concept in ?Pengumpulan Satu Juta KTP? social movement by Teman Ahok?? This study used the qualitative method. Data were collected using virtual ethnography method, with the observation of a video posted by Teman Ahok. Data were analyzed using Bormann?s Fantasy Theme Analysis. The results of this study form in three fantasy themes that describe the comments about ?Jakarta Butuh Kamu, Ayo Bergerak Sekarang? video. These themes are ?goodwill has to be supported?, ?I am ready to support Ahok, but how??, and ?Ahok is not fit to lead?. All these fantasy themes are in favor of ?it?s difficult but it is possible? rhetorical vision. The fantasy themes have emerged, and rhetorical vision is formed that linked all the fantasy themes. It can be concluded; that symbolic convergence has taken place in the dissemination of ?Jakarta Butuh Kamu, Ayo Bergerak Sekarang? video.